TOXIC EFFECTS OF GLUCOSINOLATE (ALLYL ISOTHIOCYANATE) (SYNTHETIC AND FROM MUSTARD OILCAKE) ON GROWTH AND FOOD UTILIZATION IN COMMON CARP - Hossain, M A; Jauncey, K (Indian Journal of Fisheries, 2011)
An eight week feeding trial was conducted to see the toxic effects of glucosinolate (allyl isothiocyanate)(synthetic and from mustard oilcake) on growth and food utilization in common carp (Cyprinus carpio).Toxic effect was studied histologically. Four different levels of allyl isothiocyanate from both syntheticand natural sources were tested with semi-purified diets. The response offish fed on these diets was comparedto fish fed on a fish meal based control diet (40 % protein). The results showed that diets containingupto 0.4 mg/g allyl isothiocyanate had weight gain statistically similar to those of fish fed with the controldiet. Toxic effects of glucosinolate was indicated by marked thyroid hyperplasia in fish fed with diets(4, 5, 8 and 9) containing higher levels of glucosinolate. The results however, indicated that tolerancelimit to dietary glucosinolate (allyl isothiocyanate) in carp is less than 0.4 mg/g of diet.